Post-Training Evaluation of 2021 Class VI Administrative Leadership Training for East Nusa Province at the NTT Regional Human Resources Development Agency - SALEM, Fransiskus Da Sores; NEOLAKA, Melkiesedek. N. B. C.; TODA, Hendrik (Journal of Tourism Economics and Policy, 2023)
Every ASN who holds this position must be equipped with adequate competencies in order to be able to answer a number of opportunities and challenges in realizing bureaucratic reform and increasing effectiveness in the delivery of public services and one of the regional institutions that carries out human resource training and development activities is the Resource Development Agency Human (BPSDMD) East Nusa Teggara Province. The type of research used in this research is a case study. Informants in this research will be selected purposively. In analyzing the data, the author uses the Miles and Huberman analysis model (1992:16) which states that qualitative data analysis is carried out interactively and continues continuously until completion, so the data becomes saturated. Activities in data analysis, namely data reduction, data display, verification/conclusion drawing. The results of the research found that on side (1) the input for the implementation of the 2021 Batch VI Administrative Leadership Training Training by BPSDMD NTT province includes supporting resources and basic materials needed to implement the 2021 Batch VI Administrative Leadership training policy, it is stated (1) Regulations (2) Availability of Budget (3) Organizers (4) Teaching Staff (5) Participants and (6) Facilities, while on side (b) The process of implementing the 2021 class VI Administrative Leadership Training training by BPSDMD NTT province includes (1) Methods learning and training (2) Effectiveness during the learning and training process as well as in (c) Output from the implementation of the Adminsitrator Leadership Training Training class VI in 2021 by BPSDMD NTT province.